Parâmetros nutricionais, comportamento ingestivo, desempenho, caracteristicas de carcaça e componentes não carcaça de cordeiros somalis brasileira alimentados com diferentes niveis de energia metabolizável - Aquino, Rebeca Magda da Silva (2012)
The study was conducted to evaluate the digestibility and intake of nutrients, ingestive behavior, average daily weight gain (ADG), feed conversion (FC), feed efficiency (FE),carcass characteristics, commercial’s cutting weight and yield and also internal tissue, weight of gastrointestinal content and compartments of Brazilian Somali lambs fed different levels of metabolizable energy (ME). Forty lambs, non-castrated, with average weight 13.47 ± 1.76 kg were used. Animals were distributed into five experimental treatments determined by different levels of metabolizable energy (1.18, 2.07, 2.25, 2.42 e 2.69 Mcal/kg DM) in a randomized block design with eight replicates per treatment. When the average weight of animals reaches 28 kg per treatment they were slaughtered. The intake (kg/day) for dry matter (DM), crude protein, neutral detergent fiber (NDF), fibrous carbohydrate were determined by square way (P<0.05) considering the ME. Similar behavior were (observed) to the intake of DM (g/kg0,75) and NDF (%BW e g/kg0,75). Were observed a crescent linear effect (P<0.05) to the digestibility of DM, organic matter, carbohydrate non-fibrous and quadratic effect (P<0.05) to crude protein, NDF and FC. The feeding and idle time (h/day), as well, the feed efficiency and rumination (g FDN/h) presented a quadratic effect (P<0.05), however, the feed efficiency and rumination (g DM/h) increased while the total chewing times decreased (P<0.05) through the metabolic energy level. Was observed a crescent linear effect (P<0.05) to ADG and FE, but decreased (P<0,05) to FC. The intake energy’s level influenced (P<0.05) on the linear way the empty body, loss fast, cold carcass weight and yield and by the square way the hot carcass weight and yield, loss by frozen (kg and %) and biological income. The absolute weight of all cutting shown crescent linear effect (P<0.05) with the increase of metabolizable energy levels as well as the weights to shoulder, leg and flank cuts. The ribeye evaluate by ultrasound (AOLU), fat thickness by ultrasound (EGSU) and the fat back thickness shown a linearly effect crescent (P<0.05). The measure in vivo and pós-mortem had a significant correlation (P<0.05), that shown to be moderate until high. The technique of ultrasonography was accurate, however underestimated the depth measurements ribeye and loin eye area, and fat thickness overestimated. The weight of heart, the group of organs lungs, trachea, esophagus and tongue (PTEL), kidney and spleen, in kg, shown a linearly effect (P<0.05). Similar behavior was observed by the weight to the rumen-reticulum (RURE), abomasum (ABO), small (SI) and large (LI) intestines, and perirenal, omental, of heart and mesenteric fats. It’s concluded that the increase of metabolizable energy influenced the intake and digestibility of nutrients, ingestivo behavior, and performance. The ultrasound technique can be used to estimate real kill time. The intake of metabolic energy levels provides higher commercial cuts weight and influences the weight and profit of internal tissue, viscera and fat of the Brazilian Somali lambs.